دور الخدمات الإرشادية في مساعدة المتكونين لبناء مشروعهم الشخصي بمركز التكوين المهني والتمهين - مركز التكوين المهني والتمهين الشهيد أحمد بركة - المسيلة 03 - أنموذجا - رحموني سهام; اشراف: مجاهدي الطاهر (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة إلى الكشف عن دور الخدمات الإرشادية في مساعدة المتكونين لبناء مشروعهم الشخصي بمركز التكوين المهني، مع معرفة مستوى الخدمات الإرشادية المقدمة والصعوبات المرتبطة بها لدى عينة الدراسة بمركز التكوين المهني الشهيد أحمد بركة 03 بالمسيلة. وقد اعتمدت الباحثة على المنهج الوصفي كونه الأنسب لطبيعة الموضوع المدروس، وتم إعداد أداة استبيانيه من طرف الباحثة مكونة من (33) عبارة، استوفت معايير الصدق والثبات، وللتحقق من صحة فرضيات الدراسة تم استخدام الإجراءات الإحصائية المناسبة لتحليل البيانات وتفسير النتائج، حيث توصلت الدراسة إلى مجموعة من النتائج أهمها: - للخدمات الارشادية دور في بناء المشروع الشخصي بمركز التكوين المهني الشهيد أحمد بركة بالمسيلة.03 - مستوى الخدمات الارشادية المقدمة في مركز التكوين المهني الشهيد أحمد بركة عال. - للخدمات الارشادية دور في تعزيز الثقة ومواجهة التحديات النفسية والاقتصادية. - مستوى صعوبات الاستفادة من الخدمات الارشادية بمركز التكوين المهني الشهيد أحمد بركة 03 بالمسيلة متوسط. الكلمات المفتاحية: الخدمات الإرشادية، بناء المشروع الشخصي، مركز التكوين المهني. Abstract: The aim of this study was to investigate the role of counseling services in assisting trainees to develop their personal projects at the Vocational Training Center, while assessing the level of counseling services offered and the associated difficulties among the study sample at the Vocational Training Center, Shuhada Ahmed Barka 03 in M'Sila. The researcher adopted a descriptive approach as most suitable for the nature of the study, developing a questionnaire consisting of 33 items that met validity and reliability criteria. Statistical procedures were used to analyze and interpret the data to validate the study hypotheses. The study revealed several key findings: • Counseling services play a role in the development of personal projects at the Vocational Training Center, Shuhada Ahmed Barka 03 in M'Sila. • The level of counseling services provided at the center Is high. • Counseling services contribute to enhancing confidence and addressing psychological and economic challenges. • The level of difficulties in benefiting from counseling services at the Vocational Training Center, Shuhada Ahmed Barka 03 in M'Sila, Is moderate. Keywords: Counseling services, personal project development, vocational training center.